Euler Formula Derivation - Wikaria Gazali (Engineering, MAthematics and Computer Science (EMACS) Journal, 2022)
This paper discusses the derivation of Euler's formula. To obtain this model, the writer derives Euler's formula from ex+iy by first finding the norm and argument of ex+iy. In this derivation we substitute the norm and argument of ex+iy on complex numbers in polar coordinates, until we get the derivation of Euler's formula.